(untitled) - Dorwald, Florencio Zaragoza (Weinheim, 2002)
This is the number-one successful book on solid phase organic synthesis, now in its second, expanded edition. It offers the reader · a comprehensive overview of supports, spacers, and linkers · 15% more contents · everything there is to know about reactions and their applications · clear structure · numerous experimental guidelines for use in practice The ideal reference for newcomers and experts. "... I have no doubts that this text will be the benchmark for future publications on the subject, and a very hard act to follow for authors planning books of their own on this red hot topic." The Alchemist
Hóa học các hợp chất dị vòng,Tổng hợp hữu cơ pha rắn
Keywords: Solid-phase synthesis,Tổng hợp pha- đặc